Risk factors of pediatric venoarterial extracorporeal membrane oxygenation‐related gastrointestinal bleeding after open‐heart surgeries. Issue 8 (22nd April 2022) - Yang, Yinyu; Yu, Xindi; Guo, Zheng; Zhang, Wei; Shen, Jia; Wang, Wei
Abstract: Objective: To analyze the risk factors for gastrointestinal (GI) bleeding in congenital heart disease (CHD) patients supported with venoarterial extracorporeal membrane oxygenation (V‐A ECMO) after open‐heart surgery. Methods: A retrospective analysis was performed on children with (GI group: 26 cases) and without (control group: 122 cases) GI bleeding during ECMO at Shanghai Children's Medical Center from 2017 to 2020. Clinical data were analyzed and compared between groups to search for risk factors for GI bleeding. Results: A total of 148 cases were included in the study. The overall incidence of GI bleeding was 17.6% (26/148). The in‐hospital mortality rate in the GI group was 61.5% (16/26) versus 45.9% (56/122) in the control group. Twenty‐six patients suffered cardiac arrest before ECMO support. The GI bleeding incidence among extracorporeal cardiopulmonary resuscitation (ECPR) patients was 50.0% (13/26) versus 28.7 (35/122) among non‐ECPR patients, p  = 0.035. The activated clotting time (ACT) was 201.40 s (180.47 to 247.27) in the GI group versus 177.63 s (167.79 to 203.13) ( p  = 0.050) in the control group. The lowest antithrombin level (Min AT) was 27.00 ± 13.07% versus 37.62 ± 15.18 ( p  = 0.001). The pH and lactate levels before ECMO (Pre PH and Pre Lac) were lower in the GI group than in the control group. (7.31 ± 0.23 vs. 7.35 ± 0.17, p  = 0.035 and 12.2 ± 6.11 vs. 7.78 ± 6.67, p  = 0.003). Liver function during ECMO support was statistically worse in the GI group than in the control group. Multivariate analysis showed that Pre Lac (OR = 1.106 [1.018–1.202], p  = 0.0016) was an independent risk factor for GI bleeding. ROC analysis of Pre Lac and GI bleeding showed an area under the curve (AUC) of 0.700 (95% CI: 0.600–0.800, p  = 0.002) and a cutoff value of 9.30 mmol/L (sensitivity, 73.1%; specificity, 62.7%). Conclusions: As the first study in this field, the probability of GI bleeding and related mortality was found to be high in children supported with V‐A ECMO after open‐heart surgery. A higher lactate level before ECMO was an independent risk factor for GI bleeding. Abstract : Risk factors of pediatric ECMO GI bleeding after open‐heart surgeries.